Polymorphisms within autophagy-related genes as susceptibility biomarkers for pancreatic cancer: A meta-analysis of three large European cohorts and functional characterization - Gálvez-Montosa, Fernando; Peduzzi, Giulia; Sanchez-Maldonado, José Manuel; Ter Horst, Rob; Cabrera-Serrano, Antonio J; Gentiluomo, Manuel; Macauda, Angelica; Luque, Natalia; Ünal, Pelin; García-Verdejo, Francisco José; Li, Yang; López López, José Antonio; et al. (International journal of cancer, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers with patients having unresectable or metastatic disease at diagnosis, with poor prognosis and very short survival. Given that genetic variation within autophagy-related genes influences autophagic flux and susceptibility to solid cancers, we decided to investigate whether 55,583 single nucleotide polymorphisms (SNPs) within 234 autophagy-related genes could influence the risk of developing PDAC in three large independent cohorts of European ancestry including 12,754 PDAC cases and 324,926 controls. The meta-analysis of these populations identified, for the first time, the association of the BIDrs9604789 variant with an increased risk of developing the disease (ORMeta = 1.31, p = 9.67 × 10-6). We also confirmed the association of TP63rs1515496 and TP63rs35389543 variants with PDAC risk (OR = 0.89, p = 6.27 × 10-8 and OR = 1.16, p = 2.74 × 10-5). Although it is known that BID induces autophagy and TP63 promotes cell growth, cell motility and invasion, we also found that carriers of the TP63rs1515496G allele had increased numbers of FOXP3+ Helios+ T regulatory cells and CD45RA+ T regulatory cells (p = 7.67 × 10-4 and p = 1.56 × 10-3), but also decreased levels of CD4+ T regulatory cells (p = 7.86 × 10-4). These results were in agreement with research suggesting that the TP63rs1515496 variant alters binding sites for FOXA1 and CTCF, which are transcription factors involved in modulating specific subsets of regulatory T cells. In conclusion, this study identifies BID as new susceptibility locus for PDAC and confirms previous studies suggesting that the TP63 gene is involved in the development of PDAC. This study also suggests new pathogenic mechanisms of the TP63 locus in PDAC.
Keywords: Autophagy; autophagy; transkripční faktory; duktální karcinom slinivky břišní; nádorové supresorové proteiny; jednonukleotidový polymorfismus; genetic variants; susceptibility; Pancreatic Neoplasms; polymorphisms; lidé; hepatocytární jaderný faktor 3-alfa; Polymorphism, Single Nucleotide; nádory slinivky břišní; Transcription Factors; studie případů a kontrol; genetická predispozice k nemoci; Genetic Predisposition to Disease; forkhead transkripční faktory; Hepatocyte Nuclear Factor 3-alpha; kohortové studie; autofagie; Cohort Studies; Forkhead Transcription Factors; pancreatic cancer; Tumor Suppressor Proteins; nádorové biomarkery; Case-Control Studies; Carcinoma, Pancreatic Ductal; Biomarkers, Tumor; White People; functional characterization; běloši; Humans